Does art therapy influence the quality of life of the elderly? Systematic review (Research, Society and Development, 2020)
Objective: To carry out a Systematic Review to verify the effect of Art Therapy in the quality of life of independent elderly. Methods: A systematic review was carried out based on searches in the databases: PubMed (Medline), Scopus, Web of Science, Cochrane and Lilacs, in a comprehensive and unrestricted manner to the year or language of publication. Five articles were identified for the final sample, out of a total of 1,297 initial articles. Of the articles analyzed, all responded to the research question, showing the effects of Art Therapy and the improvement in the quality of life of the elderly. Results: It was evident that Art Therapy brings benefits to those who use it. Presenting significant results, with improvements in socialization, self-esteem, quality of life, health, quality of interaction among the elderly. Conclusion: Art therapy brings benefits to the elderly, promoting health, despite the limitations generated by age, leading them to healthy aging, especially with the insertion of alternative therapies.